Retrospective evaluation of an observational cohort by the Central and Eastern Europe Network Group shows a high frequency of potential drug-drug interactions among HIV-positive patients receiving treatment for coronavirus disease 2019 (COVID-19) - Lakatos, Botond; Kowalska, Justyna; Antoniak, Sergii; Gokengin, Deniz; Begovac, Josip; Vassilenko, Anna; Wasilewski, Piotr; Fleischhans, Lukas; Jilich, David; Matulionyte, Raimonda; Kase, Kerstin; Papadopoulus, Antonios; et al. (HIV medicine, 2022)
OBJECTIVES: The aim of this international multicentre study was to review potential drug-drug interactions (DDIs) for real-life coadministration of combination antiretroviral therapy (cART) and coronavirus disease 2019 (COVID-19)-specific medications. METHODS: The Euroguidelines in Central and Eastern Europe Network Group initiated a retrospective, observational cohort study of HIV-positive patients diagnosed with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Data were collected through a standardized questionnaire and DDIs were identified using the University of Liverpool's interaction checker. RESULTS: In total, 524 (94.1% of 557) patients received cART at COVID-19 onset: 117 (22.3%) were female, and the median age was 42 (interquartile range 36-50) years. Only 115 (21.9%) patients were hospitalized, of whom 34 required oxygen therapy. The most frequent nucleoside reverse transcriptase inhibitor (NRTI) backbone was tenofovir disoproxil fumarate (TDF)/tenofovir alafenamide (TAF) with lamivudine or emtricitabine (XTC) (79.3%) along with an integrase strand transfer inhibitor (INSTI) (68.5%), nonnucleoside reverse transcriptase inhibitor (NNRTI) (17.7%), protease inhibitor (PI) (13.7%) or other (2.5%). In total, 148 (28.2%) patients received COVID-19-specific treatments: corticosteroids (15.7%), favipiravir (7.1%), remdesivir (3.1%), hydroxychloroquine (2.7%), tocilizumab (0.6%) and anakinra (0.2%). In total, 62 DDI episodes were identified in 58 patients (11.8% of the total cohort and 41.9% of the COVID-19-specific treatment group). The use of boosted PIs and elvitegravir accounted for 43 DDIs (29%), whereas NNRTIs were responsible for 14 DDIs (9.5%). CONCLUSIONS: In this analysis from the Central and Eastern European region on HIV-positive persons receiving COVID-19-specific treatment, it was found that potential DDIs were common. Although low-dose steroids are mainly used for COVID-19 treatment, comedication with boosted antiretrovirals seems to have the most frequent potential for DDIs. In addition, attention should be paid to NNRTI coadministration.
Keywords: dospělí; Female; SARS-CoV-2; Reverse Transcriptase Inhibitors; inhibitory reverzní transkriptasy; lékové interakce; Adenine; Drug Interactions; Adult; HIV séropozitivita; ženské pohlaví; Tenofovir; HIV Infections; farmakoterapie COVID-19; Anti-HIV Agents; lidé; emtricitabin; COVID-19; HIV infekce; retrospektivní studie; adenin; Male; COVID-19 Drug Treatment; lidé středního věku; tenofovir; Emtricitabine; látky proti HIV; mužské pohlaví; Retrospective Studies; Middle Aged; HIV Seropositivity; Humans